Pengaruh Sinergi Ergonomi dan Budaya Organisasi terhadap Kinerja Karyawan di Industri Kecil dan Menengah - Nurwildani, Mohammad Fajar; Padhil, Ahmad (Institut Teknologi Garut, 2025)
Employee performance improvement is a key factor in driving the competitiveness of small and medium industries (SMEs), especially in developing countries. Two important aspects that are believed to influence performance are organizational culture and ergonomics. This study aims to analyze the influence of organizational culture and ergonomics on employee performance in the SME sector. This study uses a quantitative approach with a survey method of 250 respondents selected using a saturated sampling technique. Data were analyzed using the Structural Equation Modeling (SEM) method with the help of the AMOS version 22 application. The results of the analysis show that organizational culture has a positive and significant effect on employee performance with a CR value = 2.238 and p = 0.021. Meanwhile, ergonomics also has a positive and significant effect on performance with a CR value = 2.351 and p = 0.009. These findings indicate that strengthening organizational culture and implementing ergonomic principles in the work environment play an important role in improving employee performance. Therefore, collaboration between cultural and ergonomic aspects needs to be a strategic priority in SME development.